Lentil trait preferences, gender, and varietal adoption in Ethiopia - Najjar, Dina; Nomunume Baada, Jemima; Agrawal, Shiv Kumar (2023)
presentation on Lentil trait preferences, gender, and varietal adoption in Ethiopia.